2019
DOI: 10.1016/s2095-3119(18)62090-8
|View full text |Cite
|
Sign up to set email alerts
|

Pectate lyase is a factor in the adaptability for Heterodera glycines infecting tobacco

Abstract: The soybean cyst nematode, Heterodeara glycines, is a serious pathogen of soybean, and reported to be the host of a wide range of Fabaceae. In the present study, the host specificity and reproductivity of two populations of H. glycines collected from soybean and tobacco were identified and characterized. The comparative identity between β-1,4-endoglucanase, pectate lyase and chorismate mutase of H. glycines parasitizing on soybean and tobacco were 99, 97 and 98%, respectively. The qRT-PCR analysis indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Therefore, the gene Rs-pel-3 was absent in the genomes of non-citrus parasitic populations, and the expression of Rs-pel-3 may be related to R. similis parasitism in Citrus spp.. Reportedly, the difference in pel expression in sedentary plant-parasitic nematodes is associated with their host range (Stare et al 2011;Sabeh et al 2019;Tian et al 2019). Stare et al (2011) reported that the difference in sequence polymorphism and gene copy of the pel-2 gene from Globodera was associated with the variation in the host range of G. rostochiensis, G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the gene Rs-pel-3 was absent in the genomes of non-citrus parasitic populations, and the expression of Rs-pel-3 may be related to R. similis parasitism in Citrus spp.. Reportedly, the difference in pel expression in sedentary plant-parasitic nematodes is associated with their host range (Stare et al 2011;Sabeh et al 2019;Tian et al 2019). Stare et al (2011) reported that the difference in sequence polymorphism and gene copy of the pel-2 gene from Globodera was associated with the variation in the host range of G. rostochiensis, G.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several pel genes were identified and cloned from sedentary parasitic nematodes belonging to the genera Heterodera, Globodera, and Meloidogyne, all of which belong to the Class III PEL family (Deboer et al 2002;Doyle et al 2002;Huang et al 2005;Kudla et al 2007;Vanholme et al 2007;Zhuo et al 2011;Peng et al 2012Peng et al , 2016Li et al 2017). The PEL of sedentary parasitic plant-parasitic nematodes may play an important role in host specialization and pathogenic differentiation (Huang et al 2005;Stare et al 2011;Sabeh et al 2019;Tian et al 2019). To date, only three pel genes have been identified and cloned from Bursaphelenchus xylophilus, a migratory parasitic nematode (Kikuchi et al 2006;Lee et al 2013); however, the function and mechanism of these genes and their relationship with pathogenic differentiation have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, five populations of P. coffeae showed differences in pathogenicity of N. benthamiana. These pathogenicity differences may be due to long-term adaptation of nematodes to the environment (Tian et al 2019). We found bodies and eggs of P. coffeae in the roots of N. benthamiana , indicating that P. coffeae can successfully parasitise and complete its life history in the roots of N. benthamiana , which is the same as that of peanut (Liao et al 2015), sesame (Li et al 2020), and soybean (Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…437 Another subclass of lyases is pectate lyases (PLs), which act on the degradation of pectin produced by pathogenic organisms and can potentially have industrial applications. [438][439][440][441] Chakraborty et al (2017) immobilized the recombinant Clostridium thermocellum pectate lyase in magnetite nanoparticles and, from this process, produced a biocatalyst with more signicant activity, improved thermal stability 32 times at 80 °C and 14 times at 90 °C, and with the ability to be reused for ve cycles followed by 70% of the initial activity. Its application in the biofouling of cotton fabric showed an efficient removal of pectin from the fabric surface.…”
Section: %mentioning
confidence: 99%